Optimizing the preparation conditions of cross-linked enzyme aggregates (CLEA)-protease - Mahmod, Safa Senan; Yusof, Faridah; Jami, Mohammed Saedi; Khanahmadi, Soofia (Springer Berlin Heidelberg, 2016)
Background: Cross-linked enzyme aggregate (CLEA) is considered as an effective technique in the production of immobilized biocatalysts for its industrially attractive advantages. Simplicity, stability, low cost, time saving and reusability are proved to be some of CLEA’s main advantages. Results: In this study, an active, stable and recyclable CLEA-protease from the viscera of channel catfish Ictalurus punctatus has been prepared. Optimization of the preparation parameters is carried out with the help of Response Surface Methodology. This methodology helped in studying the interaction between the most contributing factors such as cross-linker, precipitant and the additive concentrations. The optimum specific activity for CLEA-protease of 4.512 U/mg protein has shown a high stability against the denaturation forces such as temperature and pH as compared to free protease. It is further found from the study that the highest activity was achieved at the pH of 6.8 and at the temperature of 45 °C. After six cycles, CLEA-protease maintained 28 % of its original activity. Additionally, Michaelis–Menten models were used to determine the kinetic parameters i.e. Km and Vmax that helped in showing a significant difference after immobilization as compared to free protease. Conclusion: This work found that this novel CLEA-protease can be used as a very active biocatalyst in industrial applications.